BACTERIOPHAGES AND LACTIC ACID BACTERIA. UTERATURE REVIEW - V. M. Lakhtin (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
The review of literature and own data analysis describe bacteriophages application for medical microbiology (especially in cases of multiple drug resistance of pathogens) and. industrial biotechnology (the problems of decontamination and. stabilization of foods). Prospects of bacteriophages for enzyme therapy are underlined.